Key Stakeholders’ Perceptions of Motivators for Research Participation among Individuals who are Incarcerated - Hanson, Bridget L. (J Empir Res Hum Res Ethics, 2015)
Understanding motivations of research participants is crucial for developing ethical research protocols, especially for research with vulnerable populations. Through interviews with 92 IRB members, prison administrators, research ethicists, and researchers, we explored key stakeholders’ perceptions of what motivates incarcerated individuals to participate in research. Primary motivators identified were a desire to contribute to society, gaining knowledge and healthcare, acquiring incentives, and obtaining social support. The potential for undue influence or coercion were also identified as motivators. These results highlight the need for careful analysis of what motivates incarcerated individuals to participate in research as part of developing or reviewing ethically permissible and responsible research protocols. Future research should expand this line of inquiry to directly include perspectives of incarcerated individuals.